A Trustworthy Automated Short-Answer Scoring System Using a New Dataset and Hybrid Transfer Learning Method - Maslim, Martinus; Wang, Hei-Chia; Putra, Cendra Devayana; Prabowo, Yulius Denny (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2024)
To measure the quality of student learning, teachers must conduct evaluations. One of the most efficient modes of evaluation is the short answer question. However, there can be inconsistencies in teacher-performed manual evaluations due to an excessive number of students, time demands, fatigue, etc. Consequently, teachers require a trustworthy system capable of autonomously and accurately evaluating student answers. Using hybrid transfer learning and student answer dataset, we aim to create a reliable automated short answer scoring system called Hybrid Transfer Learning for Automated Short Answer Scoring (HTL-ASAS). HTL-ASAS combines multiple tokenizers from a pretrained model with the bidirectional encoder representations from transformers. Based on our evaluation of the training model, we determined that HTL-ASAS has a higher evaluation accuracy than models used in previous studies. The accuracy of HTL-ASAS for datasets containing responses to questions pertaining to introductory information technology courses reaches 99.6%. With an accuracy close to one hundred percent, the developed model can undoubtedly serve as the foundation for a trustworthy ASAS system.
Keywords: hybrid transfer learning; student answer dataset; trustworthy system; automated short; answer scoring; IJIMAI